IMPLEMENTATION OF BLENDED LEARNING IN IMPROVING THE CHARACTER OF STUDENTS THROUGH ISLAMIC RELIGIOUS EDUCATION SUBJECTS - Unik Hanifah Salsabila; Hibban Ahsanal Fata; Krisna Rasyid Alfittoh; Kory Aznam Ashari; Muhammad Rayyan Eriza (Universitas Labuhanbatu, 2023)
During the pandemic, the learning process in schools was considered less effective. The lack of involvement of students in the learning process makes learning activities only focus on the teacher. This happens because students need to adapt to the online learning process at home. Therefore, the government issued a policy for schools to implement a blended learning learning system as an effort to maximize learning, including Islamic Religious Education (PAI) lessons during the ongoing pandemic. The purpose of carrying out this research was to explore information related to the implementation of blended learning in improving the character of students through PAI subjects and direct it with library research. This research process was also carried out by exploring various kinds of data sourced from material in relevant journals in various media on the internet. This study describes the results that blended learning has been successfully used as an effective solution to optimize the PAI learning process and can overcome the deficiencies that exist in captivating and courageous learning to develop students' character. The conclusions of this study are 1) there is an effect of blended learning on optimal PAI learning objectives, 2) the need for various types of media designed in the implementation of blended learning as a form of effort to shape the character of students and learning can be achieved as well as possible.Â Keywords: Blended learning, Character Building, Islamic educationAbstrak Pada masa pandemi, proses pembelajaran di sekolah dinilai kurang efektif. Kurangnya keterlibatan peserta didik dalam proses pembelajaran menjadikan kegiatan pembelajaran hanya dipusatkan pada guru saja. Hal tersebut terjadi karena peserta didik perlu beradaptasi dengan pelaksanaan proses pembelajaran secara online di rumah. Oleh karena itu, pemerintah mengeluarkan kebijakan kepada sekolah untuk menerapkan sistem pembelajaran blended learning sebagai upaya untuk memaksimalkan pembelajaran termasuk pada pelajaran Pendidikan Agama Islam (PAI) saat masa pandemi berlangsung. Tujuan dari dilaksanakannya penelitian ini ialah untuk menggali informasi yang berkaitan dengan implementasi blended learning dalam meningkatkan karakter peserta didik melalui mata pelajaran PAI dan dilangsungkan dengan studi pustaka (library research). Proses penelitian ini dilakukan juga dengan menggali berbagai macam data yang bersumber dari materi pada jurnal-jurnal yang relevan di dalam berbagai media dalam internet. Penelitian ini memaparkan hasil bahwasannya blanded learning berhasil digunakan sebagai solusi efektif untuk mengoptimalkan proses pembelajaran PAI serta dapat mengatasi kekurangan yang ada dalam pembelajaran luring dan daring untuk mengembangkan karakter peserta didik. Simpulan penelitian ini adalah 1) adanya pengaruh blended learning terhadap pencapaian pembelajaran PAI yang optimal, 2) perlunya berbagai macam media yang dirancang dalam pelaksanaan blended learning sebagai bentuk upaya untuk membentuk karakter peserta didik dan pembelajaran dapat tercapai dengan sebaik mungkin.Kata Kunci: Blended learning, Pendidikan karakter, Pendidikan Agama Islam